OUTCOME OF TRANSURETHRAL RESECTION OF PROSTATE IN CLINICAL BENIGN PROSTATIC HYPERPLASIA - Bozdar, HR; Memon, SR; Paryani, JP (Journal of Ayub Medical College Abbottabad, 2010)
Background: Benign prostatic hyperplasia (BPH) is a condition in which the prostate gland becomes enlarged. Some men with enlarged prostate glands may experience symptoms while some may have few symptoms. Symptomatic improvement determines the successful outcome of surgical procedure of TURP for clinical BPH patients. Objectives of this study were to assess the outcome of transurethral resection of prostate (TURP) in clinical BPH with the help of International Prostate Symptom Score (IPSS). Methods: This was descriptive case series study conducted at the Department of Urology, Liaquat University of Medical and Health Sciences, Jamshoro from November 2009 to April 2010. All patients who underwent TURP for clinical BPH were included in the study. Their preoperative IPSS was done by asking irritative and obstructive symptoms. IPSS was calculated for patients who presented with urinary retention by asking lower urinary tract symptoms before urinary retention. Each symptom carried a score of 0-5, and the total score was 35. After the TURP, IPSS was calculated on 1st follow-up visit after 6 weeks and 2nd follow-up visit after 12 weeks. Outcome, was considered favourable if there was mild grade (IPSS <7) on 12th week after TRUP. Results: Total of 70 patients of clinical BPH were included in study. Mean age of the patients was 63.1±3.0 yrs. Outcome of transurethral resection of prostate was found to be favourable in 81.4% after 6 weeks in 1st follow-up visit and in 62 (88.6%) patients after 12 weeks in second follow-up visit. Preoperatively mean IPSS was 22.5 and postoperatively mean IPSS was 6.5. Conclusion: TURP is an effective and gold standard surgical treatment option in the clinical BPH patients. Keywords: Benign prostatic hyperplasia, lower urinary tract, bladder outlet obstruction, acute urinary retention, transurethral resection of prostate, TURP